Многомерный анализ социальной стратификации современного украинского общества (региональный аспект) - Ковалиско, Н.; Савчинский, Р. (Социология: теория, методы, маркетинг, 2007)
The paper summarizes the main principles of multidimensional social space analysis and their methodological potential as applied to Ukrainian society. The application of stratification model is considered on the basis of a multidimensional hierarchical approach with the use of various criteria, such as profit, educational attainment, position in the power structure, self-appraisal of financial status, self-identification, i.e.combination of both objective and subjective criteria is taken into account. The results of quantitative research of social strata at the regional level are analyzed as well.